Enfortumab vedotin plus pembrolizumab as a first-line treatment for advanced urothelial carcinoma: a cost-effectiveness analysis from China based on the EV-302 trial - You, Maojin; Zheng, Qiaoyan; He, Ying (Frontiers in Pharmacology, 2024)
Background The efficacy and safety of enfortumab vedotin combined with pembrolizumab (EV-PEMB) was investigated as a first-line treatment for advanced urothelial carcinoma (UC) in a phase III clinical trial (EV-302). The trial findings indicated significant prolonged progression-free survival (PFS) and overall survival (OS) compared to chemotherapy with a favorable safety profile. However, EV-PEMB is costly and it is unknown whether it is cost-effective compared to chemotherapy. This study aimed to conduct a cost-effectiveness analysis of EV-PEMB versus chemotherapy as a first-line treatment for advanced UC from the perspective of the Chinese healthcare system. Methods A Markov model with three distinct health states was developed to assess the cost-effectiveness of EV-PEMB as a first-line treatment for advanced UC versus chemotherapy based on the EV-302 trial. Drug costs were obtained from national tender prices. Other expenses and utility values were sourced from the literature or expert advice. The findings of the study included total costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). We conducted a one-way sensitivity analysis and probabilistic sensitivity analysis to ensure the model’s robustness. Results The EV-PEMB regimen demonstrated a gain of 3.22 QALYs at 375,420.24, compared to the chemotherapy regimen with 1.70 QALYs at 23,369.67. ICER for EV-PEMB compared to chemotherapy was at 232,256.16 per QALY gained. In China, at a willingness-to-pay threshold of 38,133 per QALY, EV-PEMB has a 0% probability of being cost-effective as a first-line treatment for advanced UC compared to chemotherapy. Conclusion From the perspective of the Chinese healthcare system, EV-PEMB is unlikely to be a cost-effective first-line treatment option for advanced UC compared to chemotherapy.